THE POTENT OF METHANOL EXTRACTS OF CASHEW (Anacardium occidentale L.) AGAINST METHICILLIN-RESISTANT Staphylococcus aureus (MRSA) - Risa Nursanty; Yunita Yunita (Jurnal Natural, 2012)
Use of antibiotics including misuse and overuse has aided natural bacterial evolution by helping the microbes become resistant such as methicillin-resistant Staphylococcus aureus (MRSA). The MRSA resistant in disease treatment with commonly used antibiotics needs new drug to treat patients. Traditional herb can be alternative treatment such as cashew (Anacardium occidentale L.). Antibacterial activities of methanol extracts of stem cashew with concentration 10%, 20% and 30% showed zone of inhibition between 17 -20 mm.